Epidemiological Trends and Risk Factors for Soccer-related Knee Injuries in Jammu & Kashmir and Punjab: A Comparative Analysis - Habib, Raheel; Anwer, Zaki; Saidan, Ghulam; Manzoor, Mehvish (Journal of Neonatal Surgery, 2025)
Background: Soccer demands exceptional agility, lower limb strength and proprioception, with high injury risks, particularly knee injuries. However, injuries are common due to the physical demands, lifestyle, and general awareness, external and internal factors. Musculoskeletal injuries, particularly knee injuries, affect both professional and recreational athletes. And their epidemiology of such injuries can be utilized for designing the prevention and training programs. This study aims to explore the epidemiological trends and risk factors of soccer-related knee injuries in Jammu and Kashmir and Punjab, two northern Indian regions. Methodology: The research used a cross-sectional, comparative design to analyze the association between knee injury trends and contributing factors in the two regions. 250 respondents were selected and a structured questionnaire was used to collect demographic information, injury patterns, environmental factors, biomechanical factors, and training and lifestyle influences. Ethical permission was secured, and statistical analysis, including descriptive statistics and correlations, was performed using SPSS (Version 26) to ascertain performance discrepancies, with a significance level of p < 0.05. Results: The study revealed significant differences in incidence and prevalence of knee injuries among players in Jammu and Kashmir and Punjab. Punjab players reported higher rates of ligament injuries and faster recovery times compared to Jammu and Kashmir players. Environmental factors, such as playing field conditions, weather, and lighting, influenced injury occurrence, accounting for 53.4% of the variation. Training and lifestyle factors, such as strength training, structured prevention programs, fitness training, stress management, and adequate sleep, also contributed to knee injury risk. Conclusion: In conclusion, the study highlighted regional differences in perceived injury risks and susceptibility, emphasizing the need for targeted interventions, addressing region-specific environmental challenges, promoting evidence-based training practices, and region-specific injury prevention strategies and enhanced player education.